Sex-Determining Gene(s) on Distal 9p: Clinical and Molecular Studies in Six Cases* - Koji Muroya; Torayuki Okuyama; Keiji Goishi; Yoshifumi Ogiso; Shin Fukuda; Junji Kameyama; Hirokazu Sato; Yoshimi Suzuki; Hiroshi Terasaki; Hiroki Gomyo; Keiko Wakui; Yoshimitsu Fukushima; et al. (2000)
Abstract We report on clinical and molecular findings in five karyotypic males (cases 1–5) and one karyotypic female (case 6) with distal 9p monosomy. Cases 1–3 and 6 had female external genitalia, case 4 showed ambiguous external genitalia, and case 5 exhibited male external genitalia with left cryptorchidism and right intrascrotal testis. Gonadal explorations at gonadectomy in cases 3 and 4 revealed that case 3 had left streak gonad and right agonadism, and case 4 had bilateral hypoplastic testes. Endocrine studies in cases 1–4 and 6 showed that cases 1, 3, and 6 had definite primary hypogonadism, with basal FSH levels of 54, 39, and 41 IU/L, respectively, whereas case 2 with severe malnutrition was unremarkable for the baseline values, and case 4 had fairly good testicular function. Fluorescence in situ hybridization and microsatellite analyses demonstrated that all cases had hemizygosity of the 9p sex-determining region distal to D9S1779, with loss of the candidate sex-determining genes DMRT1 and DMRT2 from the abnormal chromosome 9. Sequence analysis in cases 1–4 and 6 showed that they had normal sequences of each exon of DMRT1 and the DM domain of DMRT2 on the normal chromosome 9, and that cases 1–4 had normal SRY sequence. The results provide further support for the presence of a sex-determining gene(s) on distal 9p and favor the possibility of DMRT1 and/or DMRT2 being the sex-determining gene(s). Furthermore, as hemizygosity of the 9p sex-determining region was associated with a wide spectrum of gonadogenesis from agonadism to testis formation in karyotypic males and with primary hypogonadism regardless of karyotypic sex, it is inferred that haploinsufficiency of the 9p sex-determining gene(s) primarily hinders the formation of indifferent gonad, leading to various degrees of defective testis formation in karyotypic males and impaired ovary formation in karyotypic females.